Volatile compounds emitted by diverse phytopathogenic microorganisms promote plant growth and flowering through cytokinin action. (16th June 2016) - Sánchez‐López, Ángela María; Baslam, Marouane; De Diego, Nuria; Muñoz, Francisco José; Bahaji, Abdellatif; Almagro, Goizeder; Ricarte‐Bermejo, Adriana; García‐Gómez, Pablo; Li, Jun; Humplík, Jan F.; Novák, Ondřej; Spíchal, Lukáš; et al.
Abstract: It is known that volatile emissions from some beneficial rhizosphere microorganisms promote plant growth. Here we show that volatile compounds (VCs) emitted by phylogenetically diverse rhizosphere and non‐rhizhosphere bacteria and fungi (including plant pathogens and microbes that do not normally interact mutualistically with plants) promote growth and flowering of various plant species, including crops. In Arabidopsis plants exposed to VCs emitted by the phytopathogen Alternaria alternata, changes included enhancement of photosynthesis and accumulation of high levels of cytokinins (CKs) and sugars. Evidence obtained using transgenic Arabidopsis plants with altered CK status show that CKs play essential roles in this phenomenon, because growth and flowering responses to the VCs were reduced in mutants with CK‐deficiency (35S:AtCKX1) or low receptor sensitivity ( ahk2 / 3 ). Further, we demonstrate that the plant responses to fungal VCs are light‐dependent. Transcriptomic analyses of Arabidopsis leaves exposed to A. alternata VCs revealed changes in the expression of light‐ and CK‐responsive genes involved in photosynthesis, growth and flowering. Notably, many genes differentially expressed in plants treated with fungal VCs were also differentially expressed in plants exposed to VCs emitted by the plant growth promoting rhizobacterium Bacillus subtilis GB03, suggesting that plants react to microbial VCs through highly conserved regulatory mechanisms. Abstract : It is known that volatile emissions from some beneficial rhizosphere microorganisms promote plant growth. Here we show that volatile compounds (VCs) emitted by phylogenetically diverse rhizosphere and non‐rhizhosphere bacteria and fungi (including plant pathogens and microbes that do not normally interact mutualistically with plants) promote growth and flowering of various plant species, including crops. Transcriptomic analyses revealed that many genes differentially expressed in Arabidopsis plants treated with VCs emitted by the fungal phytopathogen Alternaria alternata were also differentially expressed in plants exposed to VCs emitted by the plant growth promoting rhizobacterium Bacillus subtilis GB03, suggesting that plants react to microbial VCs through highly conserved regulatory mechanisms. The discovery that VCs from pathogenic microorganisms can have beneficial effects on plant growth and development extends knowledge of the diversity and complexity of the interactions involved in modulation of plant physiology, raising questions regarding the evolution of the processes, their ecological significance and potential applications.